Genes, climate, and consumption culture : connecting the dots - Sheth, Jagdish N. (Emerald Publishing Limited, 2017)
Drawing from decades of research, Genes, Climate, and Consumption Culture: Connecting the Dots demonstrates how climate dictates culture and consumption. The author shows that human genes are climatic adaptations over thousands of years of evolution, which has resulted in the dramatic differences between people's food, clothing, and shelter choices. Most importantly, the book discusses how many of the fundamental differences between cultures, with respect to time, space, friendship, and technology, are responses to their particular climate. Readers will learn how to challenge their assumptions about what types of products and services foreign markets want. They will learn how to examine local markets vis-a-vis climate and culture, either changing their products accordingly or delivering entirely new offerings.- Resumé vydavatel
Obsahuje index.
Keywords: individuální spotřeba; člověk; klima; genetika člověka; consumption (economics); human beings; climate; human genetics; monografie; elektronické knihy; monographs; electronic books